Effect of Fiber Waviness on Tensile Strength of a Flax-Sliver-Reinforced Composite Material - Taweesak Piyatuchsananon; Akira Furuya; Baosheng Ren; Koichi Goda (Advances in Materials Science and Engineering)
Recently, a composite material made from natural fibers and biodegradable resin, “green composite,” is attracting attention as an alternative composite material for the replacement of glass fiber-reinforced plastics. Plant-based natural fibers such as kenaf and flax have already been used as composite reinforcement materials because they are more environmentally friendly and costless fibers than artificial fibers. A problem of using natural fibers is the fiber waviness, which affects the tensile properties. Fiber waviness is fluctuation in the fiber orientation that is inherent in the sliver morphology of plant-based natural fibers. This study was conducted to clarify the relation between quantified parameters of fiber waviness and a composite’s tensile strength. First, the fiber orientation angles on a flax-sliver-reinforced composite were measured. Then the angle distribution was quantified through spatial autocorrelation analysis methods: Local Moran’s I and Local Geary’s c. Finally, the relation between the resultant tensile strength and quantified parameters was discussed.